EVALUATION OF THE ANALGESIC EFFICACY OF ULTRASOUND-GUIDED FASCIA ILIACA COMPARTMENT BLOCK IN TOTAL HIP ARTHROPLASTY (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate and compare the analgesic efficacy and safety of ultrasound-guided fascia iliaca compartment block with epidural analgesia in patients undergoing total hip replacement.Subjects and methods: A prospective, randomized controlled trial was conducted on 60 patients undergoing total hip arthroplasty at Saint Paul General Hospital (from January to August 2025). Patients were randomly assigned to receive either epidural analgesia or ultrasound-guided fascia iliaca compartment block with continuous Bupivacaine 0.1%. Pain scores (VAS), Morphine requirements, procedural time, side effects, and patient satisfaction were recorded.Results: Both techniques provided effective pain relief (VAS < 4 at rest, ≈ 4 on movement). The procedure time for fascia iliaca compartment block was significantly longer (17.06 ± 3.12 min vs. 5.03 ± 1.24  min, p < 0.05). Urinary retention occurred more frequently in the epidural analgesia group (20% vs. 0%, p < 0.05). No major complications were observed, and satisfaction levels were similar between groups.Conclusion: Although ultrasound-guided fascia iliaca compartment block requires a longer performance time, it represents a safe and effective analgesic technique that provides pain control comparable to epidural analgesia, with a lower incidence of adverse effects, making it an appropriate and reliable option for patients undergoing hip arthroplasty.
Keywords: Fascia iliaca compartment block, epidural analgesia, total hip arthroplasty, postoperative pain.